2020
DOI: 10.1002/aqc.3464
|View full text |Cite
|
Sign up to set email alerts
|

Progress, opportunities and challenges for marine conservation in the Pacific Islands

Abstract: 1. The people of the Pacific have long relied on the ocean for sustenance, commerce and cultural identity, which resulted in a sophisticated understanding of the marine environment and its conservation. 2. The global declines in ocean health require new and innovative approaches to conserving marine ecosystems. Marine Protected Areas (MPAs) have been shown to be a highly effective means of conserving biodiversity and managing fisheries, while also restoring and preserving overall ecosystem function. 3. Traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
1
19
0
1
Order By: Relevance
“…Recent studies have examined the connectivity of two reefassociated species, the Easter Island spiny lobster Panulirus pascuensis Reed, 1954 and the Easter island rudderfish Kyphosus sandwicensis (Sauvage, 1880), on the western end of the Salas y Goḿez Ridge using variability of microsatellite loci (Meerhoff et al, 2018;Valencia et al, 2021). These studies found weak connectivity amongst marine fauna populations located on Rapa Nui and Salas y Goḿez Island (415 km away), findings that are consistent with other studies that indicate weak connectivity within the ridges for many reef taxa (ComitéOceanografco Nacional de Chile, 2017;Friedlander et al, 2021). In contrast, high genetic connectivity between the Desventuradas Islands and the Juan Fernandez Archipelago was described for the Juan Fernandez rock lobster Jasus frontalis (Milne Edwards, 1837) using mtDNA COI variability (Porobićet al, 2013) and the diadematid sea urchin Centrostephanus sylviae Fell 1975 using Single Nucleotide Polymorphism (SNPs) (Veliz et al, 2021).…”
Section: Genetic and Larval Connectivitysupporting
confidence: 85%
See 2 more Smart Citations
“…Recent studies have examined the connectivity of two reefassociated species, the Easter Island spiny lobster Panulirus pascuensis Reed, 1954 and the Easter island rudderfish Kyphosus sandwicensis (Sauvage, 1880), on the western end of the Salas y Goḿez Ridge using variability of microsatellite loci (Meerhoff et al, 2018;Valencia et al, 2021). These studies found weak connectivity amongst marine fauna populations located on Rapa Nui and Salas y Goḿez Island (415 km away), findings that are consistent with other studies that indicate weak connectivity within the ridges for many reef taxa (ComitéOceanografco Nacional de Chile, 2017;Friedlander et al, 2021). In contrast, high genetic connectivity between the Desventuradas Islands and the Juan Fernandez Archipelago was described for the Juan Fernandez rock lobster Jasus frontalis (Milne Edwards, 1837) using mtDNA COI variability (Porobićet al, 2013) and the diadematid sea urchin Centrostephanus sylviae Fell 1975 using Single Nucleotide Polymorphism (SNPs) (Veliz et al, 2021).…”
Section: Genetic and Larval Connectivitysupporting
confidence: 85%
“…Baseline biodiversity and ocean circulation studies will remain fundamental to understanding connectivity and will need to be complemented with new tools to generate information needed by decision makers (Borja et al, 2016;Gjerde et al, 2021). There are only a few studies that have surveyed biodiversity across the large range of the Salas y Gómez and Nazca ridges (ComiteÓ ceanografco Nacional de Chile, 2017; Friedlander et al, 2021). These studies found unique species compositions with few species shared between opposite ends of the ridges, highlighting the need to enact large-scale conservation measures to conserve representative biodiversity.…”
Section: Baseline Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These included two endemic decapods: the Juan Fernández lobster ( Jasus frontalis ), which was only observed at one station at Desventuradas in 156 m, and the Chilean golden crab ( Chaceon chilensis ), which was observed on 44% of the deployments around Desventuradas between 201 and 1,352 m. These species are currently harvested at sustainable levels by the small-scale artisanal fishers from the nearby Juan Fernández Archipelago [ 91 , 92 ]. The recently created Nazca-Desventuradas Marine Park and Mar de Juan Fernández Marine Park were strongly promoted by the Juan Fernández community to preserve their traditional lobster fishing and to exclude industrial fishing [ 93 ]. In addition, the Juan Fernández trevally ( Pseudocaranx chilensis ) and Gay’s morwong ( Nemadactylus gayi ) are both endemic to the Desventuradas and Juan Fernández archipelagos, where they are important bait for the lobster fishery [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the concept of stewardship in the Anglo-Saxon world can be traced back to the Abrahamic religions, in which humans are called upon to act as stewards of the Earth (Welchman, 2012;Al-Jayyousi, 2018) and has a legacy going back to the Middle Ages. Yet concepts of stewardship are evident in a rich diversity of local settings around the world: Japan has long traditions of landscape (satoyama) and seascape (satoumi) stewardship, Hawaii's traditional ahupua'a were governed through the kapu system of taboos, and further examples of stewardship practices of indigenous peoples have been described in Indonesia (talun-kebun), South Korea (maeulsoop), New Zealand (kaitiakitanga), the Philippines (muyong), and elsewhere (Soemarwato et al, 1985;Johannes, 1992;Berkes et al, 1995;CBD, 2011;Kahui and Richards, 2014;McMillan and Prosper, 2016;Ban et al, 2019;Lee et al, 2019;Friedlander and Gaymer, 2020). While inherently diverse and challenging to generalize, such examples illustrate a recognition of the value of nature and the communities' relationship with it, or of humans as an integral element of their respective landscapes and seascapes, often noting the necessity of harmony between humans and nature (Folke et al, 2016).…”
Section: Stewardship As a Multifaceted Moving Targetmentioning
confidence: 99%